2022
DOI: 10.1186/s13287-022-02769-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the broad application of allogeneic natural killer cell immunotherapy of cancer

Abstract: Natural killer (NK) cells are innate immune cells that recognize malignant cells through a wide array of germline-encoded receptors. Triggering of activating receptors results in cytotoxicity and broad immune system activation. The former is achieved through release of cytotoxic granules and presentation of death receptor ligands, while the latter is mediated by inflammatory cytokines, such as interferon-γ and tumor necrosis factor α. Early success with ex vivo activation of NK cells and adoptive transfer sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 125 publications
0
24
0
Order By: Relevance
“…We would predict, therefore, that the IL-15 component of this TriKE, which targets lung cancer, would also enhance infiltration of NK cells directly into the tumor, but this remains to be shown. Once within the tumor microenvironment, many challenges remain to NK cell function, such as hypoxia (58), which were not investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…We would predict, therefore, that the IL-15 component of this TriKE, which targets lung cancer, would also enhance infiltration of NK cells directly into the tumor, but this remains to be shown. Once within the tumor microenvironment, many challenges remain to NK cell function, such as hypoxia (58), which were not investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical experience with CAR-modified allogeneic NK cells has shown that they can expand and persist at low levels in vivo for at least 12 months [ 71 ]. Further research into the combination of NK cell infusions with immune checkpoint inhibitors is expected to further the likelihood of the long-term persistence and elevated activity of adoptively transferred NK cells [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind NK-DLI is the strong alloreactivity exerted by NK cells respect to tumor antigens, without inducing high rates of potentially fatal GvHD. The problem with such a therapeutic modality lies in the shortpersistence of NK cells, mainly due to the inhibition played by regulatory T-cells (Treg) and myeloid suppressor cells on one side, and by tumor-induced NK cells anergy on the other (63)(64)(65). Several strategies have focused on generating large number of NK cells persisting in vivo, to retain their efficacy in the longterm.…”
Section: Donor-derived Nk DLImentioning
confidence: 99%